Effect of Substitution of Wheat Flour and Pedada Flour (Sonneratia caseolaris) to Characteristic of White Bread - Irmawati, Irmawati; Jariyah, Jariyah; Sarofa, Ulya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
White bread is a food product generally derived from wheat flour that is consumed by the majority of people around the world. Innovations continue to be made to increase the nutritional value of bread. The use of pedada fruit (Sonneratia caseolaris) as a local food rich in fiber is an alternative to mixing with wheat flour. This study was conducted to determine the physical and organoleptic properties of wheat flour white bread with pedada flour. Organoleptic quality assessment was conducted with the participation of 25 panelists. Sensory attributes that are referenced by panelists include color, aroma, taste, texture, and overall. Data analysis used a T-test to determine the real difference between two treatments with a significant level (<0.05) including development volume, number of pores, texture, and organoleptic test. White Bread with a proportion of 80% wheat flour and 20% pedada produced a loaf volume (138.04%), porosity (11,722/cm2), and texture with texture analyzer (5,892 gf). The organoleptic test showed that the bread with 80% wheat flour and 20% pedada flour received positive ratings in terms of color and aroma, but received low ratings in terms of texture and taste.